Description of Parenting Patterns and Sanitation Hygiene in Families with Stunted Infants in Selemadeg Barat, Selemadeg, and Selemadeg Timur - Ni Made Sri Dwi Indrawati; I Gusti Agung Ayu Novya Dewi; Regina Tedjasulaksana (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Stunting is the impaired growth and development of children due to chronic malnutrition and repeated infections, characterized by below-standard length or height. The prevalence rate of stunting in Tabanan Regency in 2022 is 8.2%. The purpose of the study in general was to determine the description of parenting patterns and sanitation hygiene in families with stunted children in West Selemadeg, Selemadeg, and East Selemadeg sub-districts. This study is a descriptive study, the sampling technique was carried out by the total sampling method with a research instrument in the form of a questionnaire. Data analysis used in this study was univariate analysis. The results showed that the category of good parenting was 31% and poor parenting was 69%. Hygiene sanitation of stunted baduta is entirely in the good category. The conclusion of this research is that parenting patterns are in the poor category and sanitation hygiene is in the good categori. The suggestion from this research is to examine further the factors related to parenting pattern for toddlers and as a study for an initial survey before providing PMT subsidies. The care provided by baduta mothers should be paid attention and increase the need for food for infants that contains adequate consumption of nutrients with a composition that is in accordance with the Nutrition Adequacy Rate (AKG). Monitor growth and development since the baby is in the womb regularly so that it grows optimally.